Media Pembelajaran dan Upaya Membangun Kesadaran Belajar Siswa - Abusiri Abusiri (STAI ALHIKMAH Jakarta, 2017)
Teaching and learning process is essentially a communication process and message delivery from the presenter to the recipient. This message is delivered in verbal and non verbal communication. Instructional media play a role to support the delivery of learning message to be more standardized, interesting, effective, and efficcient. This can be done by utilizing the development of information communication technology that provides widespread opportunities in education in order to improve the educational quality. Using technology as an instructional media can make the learning process more fun and ease the comprehension, so that, the student learning awareness will grow on their own. Keywords: Instructional media, Information technology, Learning awareness Proses belajar mengajar pada hakikatnya merupakan proses komunikasi dan penyampaian pesan dari pengantar ke penerima. Pesan ini dituangkan dalam komunikasi verbal dan non verbal. Media pembelajaran berperan agar penyampaian pesan pembelajaran dapat lebih terstandar, menarik, efektif, dan efisien. Hal ini bisa dilakukan dengan memanfaatkan perkembangan teknologi informasi komunikasi yang memberikan kesempatan luas pada dunia pendidikan dalam meningkatkan mutu pendidikan. Memanfaatkan teknologi sebagai media pembelajaran membuat proses belajar dapat lebih menyenangkan danpemahamanmenjadilebihmudah, sehinggadengandemikian kesadaran belajar siswa akan tumbuh dengan sendirinya. Kata Kunci: Media pembelajaran,Teknologi informasi, Kesadaran belajar